More than a pastime - Fenella Zalfania Alfri (Nanyang Technological University, 2022)
Since the COVID-19 pandemic, limitations imposed on the public places that migrant domestic workers (MDW) gather as well as their flexibility of 'play' have further restricted their mobility—both important factors of self-expression and exercising one's identity outside the role of a MDW in Singapore. ‘More than a Pastime’ introduces a space where the pastimes, personal hobbies and creative skills of MDWs are spotlighted and given a voice to. This project acts as an exploration behind the concept of identities manifested through leisure activities and spatiality in Singapore during times of economic and societal uncertainties. It uncovers patterns of mutuality, belonging and collective expression that has emerged through interaction and shared experiences.